2014
DOI: 10.1016/j.gheart.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Isolated Right Heart Failure in Women: A Pilot Study From Western Kenya

Abstract: BackgroundSmall observational studies have found that isolated right heart failure (IRHF) is prevalent among women of sub-Saharan Africa. Further, several risk factors for the development of IRHF have been identified. However, no similar studies have been conducted in Kenya.ObjectiveWe hypothesized that specific environmental exposures and comorbidities were associated with IRHF in women of western Kenya.MethodsWe conducted a case-control study at a referral hospital in western Kenya. Cases were defined as wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Laabes et al 25 identified alcohol consumption, obesity and metabolic dysfunction as additional risk factors. Environmental factors, including poor kitchen ventilation and exposure to occupational dust, have been linked to cases of right-sided heart failure in Kenya 26. Enteroviruses and HIV have been identified as risk factors for cardiomyopathy and right-sided heart failure, respectively 26 27…”
Section: Resultsmentioning
confidence: 99%
“…Laabes et al 25 identified alcohol consumption, obesity and metabolic dysfunction as additional risk factors. Environmental factors, including poor kitchen ventilation and exposure to occupational dust, have been linked to cases of right-sided heart failure in Kenya 26. Enteroviruses and HIV have been identified as risk factors for cardiomyopathy and right-sided heart failure, respectively 26 27…”
Section: Resultsmentioning
confidence: 99%
“…Another study from Malawi among 222 adults with acute stroke and 504 non-stroke controls identified HIV as the predominant risk factor for stroke among participants ≤ 45 years [91]. A small pilot study comparing ≥ 35-year-old women with isolated right heart failure to similarly aged controls reported an adjusted odds ratio for HIV status of 40 [95% CI 3.7–441], i.e., women with heart failure had a 40-fold greater odds of having HIV compared to women without heart failure—note: wide confidence intervals reflect small sample size of 31 cases and 65 controls [92•]. A cross-sectional echocardiographic study of cardiac structure and function among children (mean 8 years) reported increased prevalence of left ventricular systolic dysfunction among those with HIV compared to those without HIV [93].…”
Section: Cvd and Hiv In Special Populationsmentioning
confidence: 99%
“…Of equal relevance as these biologically focused mechanisms are societal and environmental factors that often do not make it into cardiovascular disease prediction models. These include issues ranging from polypharmacy associated with managing multiple chronic diseases (e.g., HIV and heart failure) [131], healthcare disparities associated with HIV status that impact cardiovascular disease prevention and care [21–23], economic disparities that impact exposure to environmental pollution [92•], and clinical cardiovascular guidelines that may not account for HIV status when designating high-risk populations that could benefit from strategies beyond usual care.…”
Section: Cvd Risk Assessment and Novel Cvd Risk Factors In Hivmentioning
confidence: 99%
“…58 Women, who perform a majority of the cooking, often in poorly ventilated kitchens, endure the greatest exposure. 59 However, a direct link between household air pollution and CVDs has not yet been demonstrated. The associations between higher ambient fineparticle concentration and increased risk of IHD, stroke, and heart failure are more clear.…”
Section: Environmental Infectious and Early Life Nutritional Risk Fmentioning
confidence: 99%